2016
DOI: 10.1080/01635581.2017.1247892
|View full text |Cite
|
Sign up to set email alerts
|

Application of Probabilistic Modeling to Quantify the Reduction Levels of Hepatocellular Carcinoma Risk Attributable to Chronic Aflatoxins Exposure

Abstract: Epidemiological studies show a definite connection between areas of high aflatoxin content and a high occurrence of human hepatocellular carcinoma (HCC). Hepatitis B virus in individuals further increases the risk of HCC. The two risk factors are prevalent in rural Kenya and continuously predispose the rural populations to HCC. A quantitative cancer risk assessment therefore quantified the levels at which potential pre- and postharvest interventions reduce the HCC risk attributable to consumption of contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…This thus shows that AFM 1 from milk consumption contributes very little to the annual incidence rate for liver cancer. In general, the incidence rates for HCC reported here are comparable to estimates for Gambia [18] but relatively lower than those reported from a risk assessment in Kenya based on aflatoxin exposure from groundnuts [32] and maize [18]. The latter study reported an incidence rate of 29.2 and 11 cancers per year per 100,000 population from maize collected from rural markets and commercial markets, respectively.…”
Section: Discussionsupporting
confidence: 65%
“…This thus shows that AFM 1 from milk consumption contributes very little to the annual incidence rate for liver cancer. In general, the incidence rates for HCC reported here are comparable to estimates for Gambia [18] but relatively lower than those reported from a risk assessment in Kenya based on aflatoxin exposure from groundnuts [32] and maize [18]. The latter study reported an incidence rate of 29.2 and 11 cancers per year per 100,000 population from maize collected from rural markets and commercial markets, respectively.…”
Section: Discussionsupporting
confidence: 65%
“…The first recorded acute human aflatoxicosis outbreak in Kenya occurred in 1981 involving 12 fatalities (Ngindu et al, 1982), while the second occurred in the 2004-2005 cropping season (Lewis et al, 2005) with both incidents occurring in lower eastern Kenya. High aflatoxins concentrations in food, serum aflatoxin B 1 -lysine adduct concentrations and positive hepatitis B surface antigen titres have been identified as risk indicators for aflatoxicosis and hepatocellular carcinoma in Kenyan populations (Azziz-Baumgartner et al, 2005;Wambui et al, 2016a).…”
Section: Aflatoxins and Healthmentioning
confidence: 99%
“…AFM 1 was detected in 100% of the breast milk samples in Kenya and the PDI was estimated in the range of 1.13 to 66.79 ng/kg bw per day for the infants (Wambui, Karuri, Ojiambo, & Njage, 2017). In Egypt, AFM 1 was detected in 65% of the breast milk samples above 0.05 µg/L of 150 mothers of infants fed exclusively on breast milk.…”
Section: Resultsmentioning
confidence: 99%
“…Wambui et al. (2017) estimated that reductions in the occurrence of HCC among rural dwellers in Kenya could be achieved through combinations of various agronomic measures, such as the use of farmyard manure, lime in groundnut, and the use of nonaflatoxigenic strains.…”
Section: Resultsmentioning
confidence: 99%